Dictyobacter vulcani sp. nov., belonging to the class Ktedonobacteria, isolated from soil of the Mt Zao volcano. Issue 3 (23rd January 2020) - Zheng, Yu; Wang, Chiung-mei; Sakai, Yasuteru; Abe, Keietsu; Yokota, Akira; Yabe, Shuhei
Abstract : An aerobic, Gram-stain-positive, mesophilic Ktedonobacteria strain, W12 T, was isolated from soil of the Mt Zao volcano in Miyagi, Japan. Cells were filamentous, non-motile, and grew at 20–37 °C (optimally at 30 °C), at pH 5.0–7.0 (optimally at pH 6.0) and with <2 % (w/v) NaCl on 10-fold diluted Reasoner's 2A (R2A) medium. Oval-shaped spores were formed on aerial mycelia. Strain W12 T hydrolysed microcrystalline cellulose and xylan very weakly, and used d -glucose as its sole carbon source. The major menaquinone was MK-9, and the major cellular fatty acids were C16 : 1 2-OH, iso-C17 : 0, summed feature 9 (10-methyl C16 : 0 and/or iso-C17 : 1 ω9 c ) and anteiso-C17 : 0 . Cell-wall sugars were mannose and xylose, and cell-wall amino acids were d -glutamic acid, glycine, l -serine, d -alanine, l -alanine, β-alanine and l -ornithine. Polar lipids were phosphatidylinositol, phosphatidylglycerol, diphosphatidylglycerol, an unidentified glycolipid and an unidentified phospholipid. Strain W12 T has a genome of 7.42 Mb with 49.7 mol% G+C content. Nine copies of 16S rRNA genes with a maximum dissimilarity of 1.02 % and 13 biosynthetic gene clusters mainly coding for peptide products were predicted in the genome. Phylogenetic analysis based on both 16S rRNA gene and whole genome sequences indicated that strain W12 T represents a novel species in the genus Dictyobacter . The most closely related Dictyobacter type strain was Dictyobacter alpinus Uno16 T, with 16S rRNA gene sequence similarity and genomic average nucleotide identity of 98.37 % and 80.00 %, respectively. Herein, we propose the name Dictyobacter vulcani sp. nov. for the type strain W12 T (=NBRC 113551 T =BCRC 81169 T ) in the bacterial class Ktedonobacteria .